Alkali metals dancing with 4, 5-bis(1-hydroxytetrazol-5-yl)-2H-1, 2, 3-triazole: A family of energetic coordination polymers as prospective "green" pyrotechnics. (December 2022) - Luo, L.; Jin, B.; Hao, W.; Zhang, J.; Huang, T.; Peng, R.
Abstract: Energetic coordination polymers (ECPs) with alkali metals remain at the forefront of pyrotechnics research due to their enormous potential for improving the safety and compatibility of pyrotechnics. Herein, we selected 4, 5-bis(1-hydroxytetrazol-5-yl)-2H-1, 2, 3-triazole (H3 OBTT) as the energetic linker because of its high nitrogen content (64.98%), abundant coordination sites, and good thermal stability ( T p = 246 °C). A family of new ECPs, namely, [Li2 (HOBTT) (H2 O)]n ·2H2 O (1 ), [Na2 (HOBTT)(H2 O)2 ]n ·H2 O (2 ), [K(H2 OBTT)]n (3 ), and [Cs2 (HOBTT)]n (4 ), were successfully prepared and characterized. Among them, 3 and 4 displayed three-dimensional solvent-free frameworks. They exhibit excellent thermal stabilities ( T dec >280 °C) and mechanical sensitivities ( IS > 40 J, FS > 250 N). The flame colors of 1 –4 were largely due to the unique excitation of different alkali metals ranging from red to yellow. The dynamic combustion of 1 –4 discovered that the combustion duration of 3 was more than 1.720 s, and its flame stability time reached 1.400 s. Additionally, 3 was simple to prepare under mild conditions with a short reaction time, making it prospective "green" pyrotechnic candidates. Highlights: Energetic coordination polymers (ECPs) with alkali metals, [Li2 (HOBTT) (H2 O)]n ·2H2 O (1 ), [Na2 (HOBTT)(H2 O)2 ]n ·H2 O (2 ), [K(H2 OBTT)]n (3 ), and [Cs2 (HOBTT)]n (4 ), were successfully prepared and characterized. ECPs 1-4 exhibit excellent thermal stabilities ( T dec >280 °C) and mechanical sensitivities ( IS > 40 J, FS > 250 N). The simple preparation, mild-condition requirement, and short time consumption of ECP 3 indicated its potential application in "green" pyrotechnics.